How does policy innovation diffuse among Chinese local governments? A qualitative comparative analysis of River Chief Innovation. (25th January 2021) - Zhang, Yunxiang; Wang, Shichen
Abstract: It is well‐documented that interlocal learning and competition could drive policy innovation diffusion. However, their interconnection in non‐western regimes as China is less explored. Utilizing the method of qualitative comparative analysis on the case of River Chief Innovation, this article intends to explore the multiple conjunctural causation of Chinese policy diffusion and the impacts of central recognition. Our findings suggest that interlocal learning and tournament could intimately stimulate Chinese policy diffusion through different combinations. Different governments would adopt innovation for various reasons in a continuum of diffusion mechanisms, involving the technical learning, the championship‐induced learning, the mandate‐induced learning, and the innovation tournament. Hence, despite the ongoing centralization under Xi, space for local spontaneous learning remains. We also find that central recognition could activate the interlocal tournament and extend the diffusion continuum to the tournament side. Therefore, it facilitates policy diffusion toward governments that lack learning motivations and promotes the local implementation of central preferences.